Observations on two Procamallanus (Spirocamallanus) species (Nematoda: Camallanidae) from freshwater fishes in Argentina, including description of Procamallanus (Spirocamallanus) juana sp.nov. - Ramallo, Geraldine; Ailán-Choke, Lorena Gisela (Zootaxa, 2017)
Helminthological examination of specimens of the freshwater fishes Pimelodus albicans Valenciennes (Pimelodidae), Pimelodella gracilis (Valenciennes) (Heptapteridae) and Hyphessobrycon anisitsi Eigenmann (Characidae), collected from the Salado River, province of Santiago del Estero, Argentina, revealed the presence of two species of parasitic nematodes, Procamallanus (Spirocamallanus) juana sp. nov. and Procamallanus (Spirocamallanus) hilarii (Camallanidae). Procamallanus (Spirocamallanus) juana sp. nov. was characterized by the presence of six visible pores located around the oral opening in both sexes, 14 cephalic papillae, buccal capsule with 5-7 spiral thickenings, three pairs of preanal papillae, and three pairs of postanal papillae, and conspicuous and pre-equatorial vulva in females. Procamallanus (Spirocamallanus) hilarii was recorded for the first time in Hyphessobrycon anisitsi from northern Argentina. Moreover, zoogeographical and host information for the genus Procamallanus (Spirocamallanus) is summarized.